Management of dynamic production networks from a critical chain perspective - Tenera, Alexandra (2008)
Collaborative networks are typically assumed to bring clear benefits and competitive advantage to the participating members. However, as the networks are typically formed by heterogeneous and autonomous enterprises, the development of methodologies that facilitates the management process is an important element for the wide adoption of this paradigm. Departing from a brief presentation of Critical Chain Project Management Concepts, this paper introduces an approach of these concepts to collaborative networks and discusses its potential application in the context of a dynamic production networks. Finally, experimental results based on data from a network in construction industry are presented.